Improved extractability of carotenoids from tomato peels as side benefits of PEF treatment of tomato fruit for more energy-efficient steam-assisted peeling. (September 2018) - Pataro, G.; Carullo, D.; Bakar Siddique, Md A.; Falcone, M.; Donsì, F.; Ferrari, G.
Abstract: The combination of steam blanching (SB) with Pulsed Electric Fields (PEF) treatments of whole tomatoes, in addition to reducing the energy required for tomato peeling, can significantly contribute to the recovery of carotenoids from the peels. In this work, PEF (0.25-0-75 kV/cm, 1 kJ/kg) and SB (1 min at 50–70 °C), as pre-treatment prior to hand peeling, were investigated to assess their ability, separately and in combination, to induce the cell permeabilization of tomato peels, and hence to improve the carotenoids extraction in acetone (4 h at 25 °C). PEF and SB, by inducing significant damages at the cuticular level, caused the increase of the yield in total carotenoids (up to 188% for PEF and 189% for SB) and antioxidant power (up to 372% for PEF and 305% for SB) with respect to the peels from untreated tomatoes. The application of a combined treatment (PEF + SB) significantly increased the carotenoid content and the antioxidant power of the extracts, with a synergistic effect observed already at 60 °C (37.9 mg/100 g fresh weight tomato peels). HPLC analyses revealed that lycopene was the main carotenoid extracted and that neither PEF nor SB caused any selective release or degradation of lycopene. Results obtained from this study demonstrate that the integration of PEF in the processing line of tomato fruits prior to SB contributes to the valorization of tomato processing by-products. Highlights: PEF is combined with steam blanching (SB) to intensify carotenoids extraction. PEF and SB treatments of whole tomatoes induced peel damages at cuticular level. Combined PEF and SB showed a synergistic effect on carotenoids recovery from peels. All-trans-lycopene was the most abundant carotenoid in tomato peels extract. PEF and SB did not cause any degradation/isomerization of lycopene.